2021
DOI: 10.3390/polym13213642
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Low-Velocity Impact of Carbon Fibre-Based Non-Crimp Fabric Reinforced Thermoplastic Composites

Abstract: There has been a lot of interest in understanding the low-velocity impact (LVI) response of thermoplastic composites. However, little research has focussed on studying the impact behaviour of non-crimp fabric (NCF)-based fibre reinforced thermoplastic composites. The purpose of this study was to evaluate the LVI responses of two types of non-crimp fabric (NCF) carbon fibre reinforced thermoplastic laminated composites that have been considered attractive in the automotive and aerospace industry: (i) T700/polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…These materials were supplied by partners in the THERMOCOMP project [ 29 ]. The T700/PA6.6 material system has also previously been reported and discussed in Mohsin et al [ 24 , 32 ].…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…These materials were supplied by partners in the THERMOCOMP project [ 29 ]. The T700/PA6.6 material system has also previously been reported and discussed in Mohsin et al [ 24 , 32 ].…”
Section: Methodsmentioning
confidence: 87%
“…One of the most useful real-world applications of composites is low-velocity impact, as laminated composites have been proven to be capable of absorbing higher impact energy compared to conventional metals and metal alloys [ 24 , 25 ]. Mohsin et al [ 24 ] have proven that thermoplastic composites are superior to most thermosetting composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray μCT systems are used to observe fibrous composites to evaluate damage after impact. Composites made with non-crimped, carbon-fibre-reinforced thermoplastic laminations were subjected to an impact force provided by a hemispherical impactor with a 16 mm diameter, and the resulting damage was observed using an X-ray μCT system [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mohsin et al [ 9 ] performed a numerical and experimental study on the low-velocity impact response of non-crimp fabric-based composites and reported rebounding, penetration, or perforation of the impactor as possible outcomes. Matrix cracking, delamination, fibre matrix debonding, and fibre fracture were identified as probable failure modes at different stages of the laminate response.…”
Section: Introductionmentioning
confidence: 99%